Epidemiology and genetics of microtia-anotia: a registry based study on over one million births. Issue 6 (June 1995) - Mastroiacovo, P; Corchia, C; Botto, L D; Lanni, R; Zampino, G; Fusco, D
Abstract : The epidemiology and genetics of microtia-anotia (M-A) were studied using data collected from the Italian Multicentre Birth Defects Registry (IPIMC) from 1983 to 1992. Among 1, 173, 794 births, we identified 172 with M-A, a rate of 1.46/10, 000; 38 infants (22.1%) had anotia. Of the 172 infants, 114 (66.2%) had an isolated defect, 48 (27.9%) were multiformed infants (MMI) with M-A, and 10 (5.8%) had a well defined syndrome. The frequency of bilateral defects among non-syndromic cases was 12% compared to 50% of syndromic cases (p = 0.007). Among the MMI only holoprosencephaly was preferentially associated with M-A (four cases observed upsilon 0.7 expected, p = 0.005). No significant variations were identified in the prevalence of non-syndromic cases by geographical area (range 0.62-2.37/10, 000 births) or by five month time periods (range 0.21-2.58/10, 000 births), nor was there evidence of time trends. When M-A cases were compared to controls, we found that mothers with parity 1 had a higher risk of giving birth to an MMI with M-A, and that mothers with chronic maternal insulin dependent diabetes were at significantly higher risk for having a child with M-A. MMI with M-A had higher rates of prematurity, low birth weight, reduced intrauterine growth, and neonatal mortality than infants with isolated M-A and controls. Babies with isolated M-A had, on average, a lower birth weight than controls; the difference was higher for females. The analysis of pedigrees and familial cases suggests an autosomal dominant trait with variable expression and incomplete penetrance in a proportion of cases, or a multifactorial aetiology. Three cases had consanguineous parents, but the absence of M-A among previous sibs does not support autosomal recessive inheritance.